Breathlessness is associated with urinary incontinence in men: A community-based study - Hirayama, Fumi; Lee, Andy; Hiramatsu, T.; Tanikawa, Y. (BioMed Central Ltd, 2010)
Background: Urinary incontinence (UI) is a distressing problem for older people. To investigate the relationship between UI and respiratory symptoms among middle-aged and older men, a community-based study was conducted in Japan. Methods: A convenience sample of 668 community-dwelling men aged 40 years or above was recruited from middle and southern Japan. The International Consultation on Incontinence Questionnaire-Short Form, the Medical Research Council's dyspnoea scale and the Australian Lung Foundation's Feeling Short of Breath scale, were administered by face-to-face interviews to ascertain their UI status and respiratory symptoms. Results: The overall prevalence of UI was 7.6%, with urge-type leakage (59%) being most common among the 51 incontinent men. The presence of respiratory symptoms was significantly higher among incontinent men than those without the condition, especially for breathlessness (45% versus 30%, p = 0.025). The odds of UI for breathlessness was 2.11 (95% confidence interval 1.10-4.06) after accounting for age, body mass index, smoking and alcohol drinking status of each individual. Conclusions: The findings suggested a significant association between UI and breathlessness in middle-aged and older men.